Converting Insulin-like Growth Factors 1 and 2 into High-Affinity Ligands for Insulin Receptor Isoform A by the Introduction of an Evolutionarily Divergent Mutation - Macháčková, Kateřina; Chrudinová, Martina; Radosavljević, Jelena; Potalitsyn, Pavlo; Křížková, Květoslava; Fábry, Milan; Selicharová, Irena; Collinsová, Michaela; Brzozowski, Andrzej M; Žáková, Lenka; Jiráček, Jiří (Biochemistry, 2018)
Insulin-like growth factors 1 and 2 (IGF-1 and -2, respectively) are protein hormones involved not only in normal growth and development but also in life span regulation and cancer. They exert their functions mainly through the IGF-1R or by binding to isoform A of the insulin receptor (IR-A). The development of IGF-1 and IGF-2 antagonists is of great clinical interest. Mutations of A4 and A8 sites of human insulin lead to disproportionate effects on hormone IR binding and activation. Here, we systematically modified IGF-1 sites 45, 46, and 49 and IGF-2 sites 45 and 48, which correspond, or are close, to insulin sites A4 and A8. The IGF-1R and IR-A binding and autophosphorylation potencies of these analogues were characterized. They retained the main IGF-1R-related properties, but the hormones with His49 in IGF-1 and His48 in IGF-2 showed significantly higher affinities for IR-A and for IR-B, being the strongest IGF-1- and IGF-2-like binders of these receptors ever reported. All analogues activated IR-A and IGF-1R without major discrepancies in their binding affinities. This study revealed that IR-A and IGF-1R contain specific sites, likely parts of their so-called sites 2', which can interact differently with specifically modified IGF analogues. Moreover, a clear importance of IGF-2 site 44 for effective hormone folding was also observed. These findings may facilitate novel and rational engineering of new hormone analogues for IR-A and IGF-1R studies and for potential medical applications.
Keywords: mutace; receptor IGF typ 1; receptory somatomedinů; Insulin-Like Growth Factor I; vazba proteinů; lidé; signální transdukce; Insulin; Evolution, Molecular; molekulární evoluce; Mutation; Receptor, IGF Type 1; Receptor, Insulin; Signal Transduction; Phosphorylation; Ligands; Humans; insulinu podobný růstový faktor II; insulinu podobný růstový faktor I; fosforylace; Protein Isoforms; protein - isoformy; Receptors, Somatomedin; receptor inzulinu; inzulin; Protein Binding; ligandy; Insulin-Like Growth Factor II